Graphene-anchored NiCoO2 nanoarrays as supercapacitor electrode for enhanced electrochemical performance. (10th September 2017) - Zhu, Yingfang; Huang, Haifu; Li, Guangxu; Liang, Xianqing; Zhou, Wenzheng; Guo, Jin; Wei, Wenlou; Tang, Shaolong
Graphical abstract: Highlights: Porous flower-like NiCoO2 /rGO/NFnanoarrays were grown directly on Ni foam without any binders by ahydrothermal method. NiCoO2 /rGO/NFshowshigh specific capacity (1286 C g -1 )and outstandingrate capability (1071.5 C g -1 at 12 A g -1 ). The excellentperformance is attributed to the introduction of graphene into the ultrathin NiCoO2 nanoflakes. It demonstrates the potential application of NiCoO2 /rGO/NF compositeas an electrode material for supercapacitors. Abstract: Porous flower-like NiCoO2 and graphene (NiCoO2 /rGO) composite nanoarrays were grown directly on Ni foam (NF) without any binders by a simple hydrothermal synthesis method. Due to the porous flowers-like architecture of ultrathin NiCoO2 nanoflakes and the introduction of graphene with the high electrical conductivity, NiCoO2 /rGO composite nanoarrays showed superior electrochemical performance including high specific capacity (1286C g −1 at 0.5 A g −1 ), and good rate capability (1071.5C g −1, 83.3% capacity retention at 12 A g −1 ). The asymmetric supercapacitor assembled with NiCoO2 /rGO and rGO/NF also showed good performance with the energy density of 38.5 Wh kg −1 at 288 W kg −1 power density and good cycle stability of 86.9% after 2000 cycles. These results demonstrate the potential application of NiCoO2 /rGO composite nanoarrays as a promising electrode material for supercapacitors.